Por uma Igreja em saída a partir do Papa Francisco: desafios para uma evangelização hoje - Amaral, Emerson de Almeida (2024)
The present research aims to investigate the challenges of the Church's evangelizing action, based on the ecclesiology of Pope Francis, in the expression “Church on the way out”. Given the current insufficient evangelizing proposals, there is a great disconnect between pastoral life and contemporary culture. This is evident when one realizes the desire for a return to the ecclesiastical style of Christianity and the forgetfulness of a new time called post-modernity, with the challenge of centralizing the individual, rejecting any type of institution that places limits on the individualization of life. In a fight against the diseased pastoral care of maintenance, conservative, closed, schismatic and self-referential, with centralizing, authoritarian, oppressive, exclusionary and combative tendencies, a reflection will be shaped on the possibility of an evangelization capable of reaching people, with their expectations and your way of being. And, faced with a deafness to the voice of the Church, where its message is ignored, in an attitude of indifference or irrelevance, it is necessary to return to the sources of Christianity, sharpening people's sensitivity, in a conciliar pastoral dynamic. The research is limited to a bibliographic research methodology. From a formal point of view, the research problem was formulated as follows: what are the challenges for the evangelization of an Outgoing Church in contemporary times? The expected results are limited to the discussions that may arise and which will certainly shed light on the challenges of the Outgoing Church. We understand that the more discussions are provoked about the plausible paths of effective and relevant evangelization, the more chances for improvements. Therefore, this research aims to point towards a path that can lead to the appreciation of the message of the Catholic Church in dialogue with the changes in the world today, signaling the mission, in the light of Pope Francis, as a fundamental axis for a relevant pastoral, committed to the ethics of otherness and the discernment of the signs of the times, in a synodal spirit